Countries Manufacturing Pharmaceuticals for the US Market: A 10-Year Analysis of Public Data. Issue 10 (October 2022) - Hatton, Randy C.; Leighton, Greg; Englander, Libbe
Background: Concerns about strategic supplies and quality have increased the scrutiny of the countries where US pharmaceuticals are made. Objective: To examine the locations of manufacturers of brand name, biological, and generic drugs over 10 years. Methods: This longitudinal descriptive study used publicly available data from US government Web sites, including the Food and Drug Administration (FDA) Drug Establishments list, FDA National Drug Code Directory, FDA Orange Book, FDA Purple Book, and the National Institutes of Health DailyMed Drug Labels. These data were collected from 2011 to 2020. Results: Brand name drug manufacturing in the United States and Europe decreased from 89% in 2011 to 79% in 2020. Biological manufacturing in the United States decreased, while that in Western European countries increased; 100% of biological manufacturing was done in the United States or Europe in 2011 and decreased to 93% by 2020. Generic manufacturing in India increased from 21% to 51%, while US manufacturing decreased from 52% to 35% from 2011 to 2020. These analyses were limited to publicly available data, and the results could be affected by the accuracy and completeness of the data. Conclusions and relevance: Brand name drugs and biologicals are primarily made in the United States and Europe. Generic drugs are increasingly made in India, but the United States remains a major supplier. If the country of origin for pharmaceuticals is important, these findings support supply chain concerns for generic drugs. We recommend that product containers and official labeling prominently include the manufacturer and location for active pharmaceutical ingredients and finished dosage forms.